Transformasi Digital dalam Pengelolaan Data Hewan Kurban Berbasis Web di Masjid Baiturahhman - Sitti Aliyah Azzahra; Adi Wicaksono (Fakultas Teknik Universitas Cenderawasih, 2024)
This community service activity aims to develop a web app for the management of sacrificial animal operations, covering the entire process from ordering to meat distribution. The development methodology integrates Agile, DevOps, and Design Thinking. The study focuses on Masjid Baiturrahman located at Jl. Legoso Raya No. 31B, RT 06 RW 07, Pisangan Village, Ciputat Timur District, South Tangerang City. Agile methodology ensures iterative and adaptive development based on user feedback. DevOps automates integration and ensures continuous delivery, facilitating rapid and reliable deployment. Design Thinking guides user-centered solution design through stages of empathize, define, ideate, prototype, and test. This activity resulted in a web-based application that can be used by the management of DKM Masjid Baiturrahman for managing sacrificial animal data. This web-based application is capable of enhancing efficiency, accuracy, and transparency in all stages of the ordering, slaughtering, and meat distribution processes. Moreover, it assists DKM in digitally managing sacrificial animal data, ultimately improving operational performance and congregational trust in the sacrificial process.